2016
DOI: 10.11646/phytotaxa.267.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Butyriboletus hainanensis (Boletaceae, Boletales), a new species from tropical China

Abstract: Butyriboletus hainanensis (Boletaceae, Boletales) is described as a new species from Hainan Province, a tropical region of China. It is morphologically characterized by a large, brown pileus with thick context and thin hymenophore, a blue-red-black color change of hymenophore and context, a yellow to brownish red stipe with faint reticulations, and an interwoven trichodermal pileipellis. Phylogenetic analyses of DNA sequences from partial 28S regions,  the translation elongation factor 1-α gene (tef1α) and RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 1 publication
2
12
0
Order By: Relevance
“…Zeng et al, But.pseudospeciosus Kuan Zhao & Zhu L.Yang, But.roseoflavus (Hai B.Li & Hai L.Wei) D.Arora & J.L.Frank, But.sanicibus D. Arora & J.L.Frank, But.subsplendidus (W.F. Chiu) Kuan Zhao et al, and But.yicibus D. Arora & J.L.Frank have been described from China (Arora and Frank 2014; Liang et al 2016; Wu et al 2016a). Herein, we describe another novel species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zeng et al, But.pseudospeciosus Kuan Zhao & Zhu L.Yang, But.roseoflavus (Hai B.Li & Hai L.Wei) D.Arora & J.L.Frank, But.sanicibus D. Arora & J.L.Frank, But.subsplendidus (W.F. Chiu) Kuan Zhao et al, and But.yicibus D. Arora & J.L.Frank have been described from China (Arora and Frank 2014; Liang et al 2016; Wu et al 2016a). Herein, we describe another novel species.…”
Section: Resultsmentioning
confidence: 99%
“…Subtropical and tropical China is believed to be a biodiversity hotspot. Mycologists have paid much attention to boletes of the region in the past decade, and many taxa have been discovered (Bi et al 1997; Zeng and Yang 2011; Zeng et al 2012, 2013, 2014a, b, 2015a, b, 2016, 2017, 2018; Zang 2013; Liang et al2016, 2017, 2018; Chai et al 2018; Xue et al 2018). Among of them, many have been found to be as North American or European species (Bi et al 1997; Zang 2013), and recent studies have shown that species shared between subtropical/tropical China and North America/Europe are rare but that there are many common species between Japan and subtropical/tropical China (Zeng et al 2013, 2016, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baker) Wolfe and A. subvirens (Hongo) Wolfe were reported in previous studies [1,[12][13][14][15]. Hainan, a tropical area covered mostly by rainforests, is considered as a hotspot of biodiversity, and many new taxa of macrofungi were described from the region in the past [16][17][18][19][20][21][22][23][24][25]. With further investigations, more new taxa are expected to be uncovered.…”
Section: Introductionmentioning
confidence: 85%
“…The separation of Neoboletus from Boletus s. str. and its establishment at the generic rank is phylogenetically strongly supported (Binder and Hibbett 2006, Mello et al 2006, Halling et al 2007, 2015; Desjardin et al 2009, Li et al 2011, Zeng et al 2012, Gelardi et al 2013, 2015; Nuhn et al 2013, Trappe et al 2013, Arora and Frank 2014, Vizzini et al 2014, Wu et al 2014, Zhao et al 2014, 2015; Zhu et al 2014, Chakraborty et al 2015, Simonini and Vizzini 2015, Smith et al 2015, Urban and Klofac 2015, Henkel et al 2016, Liang et al 2016, Orihara and Smith 2017), the genus being tentatively placed in the “Pulveroboletus group” (Wu et al 2014), although its taxonomic placement within the Boletaceae still remains uncertain (Nuhn et al 2013, Wu et al 2014).…”
Section: Introductionmentioning
confidence: 99%